Neonatal hypothermia and associated factors among neonates admitted to neonatal intensive care unit of public hospitals in Addis Ababa, Ethiopia - Demissie, Birhanu Wondimeneh (BMC Pediatr, 2018)
BACKGROUND: Neonatal hypothermia is a worldwide problem and an important contributing factor for Neonatal morbidity and mortality especially in developing countries. High prevalence of hypothermia has been reported from countries with the highest burden of Neonatal mortality. So the aim of this study was to assess the prevalence of Neonatal hypothermia and associated factors among newborn admitted to Neonatal Intensive Care Unit of Public Hospitals in Addis Ababa. METHODS: An institutional based cross-sectional study was conducted from March 30 to April 30, 2016, in Public Hospitals in Addis Ababa and based on admission rate a total of 356 Neonates with their mother paired were enrolled for the study. Axillary temperate of the newborn was measured by a digital thermometer at the point of admission. Multivariate binary logistic regression, with 95% confidence interval and a p-value < 0.05 was used to identify variables which had a significant association. RESULTS: The prevalence of Neonatal hypothermia in the study area was 64%. Preterm delivery (AOR = 4.81, 95% CI: 2.67, 8.64), age of Neonate ≤24 h old (AOR = 2.26, 95% CI: 1.27, 4.03), no skin to skin contact with their mother immediately after delivery (AOR = 4.39, 95% CI: 2.38, 8.11), delayed initiation of breastfeeding (AOR = 3.72, 95% CI: 2.07, 6.65) and resuscitation at birth (AOR = 3.65, 95%CI: 1.52, 8.78) were significantly associated with hypothermia. CONCLUSIONS: The prevalence of Neonatal hypothermia in the study area was high. Preterm delivery, age ≤ 24 h old, no skin to skin contact immediately after delivery, delayed initiation of breastfeeding and resuscitation at birth were independent predictors of Neonatal hypothermia. Therefore attention is needed for thermal care of preterm newborn and use of low-cost thermal protection principles of warm chain especially on early initiation of breastfeeding, skin to skin contact immediately after delivery and warm resuscitation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12887-018-1238-0) contains supplementary material, which is available to authorized users.